Exodus : a commentary on the Greek text of Codex Vaticanus - Gurtner, Daniel M. (Septuagint Commentary Series., 2013)
Exodus: A Commentary on the Greek Text of Codex Vaticanus is the first comprehensive commentary on the Septuagint in English. An introduction orients readers to the study of LXX Exodus and the manuscript of Codex Vaticanus. This is followed by a presentation of the text of Vaticanus opposite a fresh translation. In the commentary proper, Gurtner examines literary features of the Greek of Exodus in general as well as features particular to the text of Vaticanus. Some comparisons are made with other Greek traditions of Exodus in addition to translational features of Exodus with respect to its Vorlage.